KRITIK SOSIAL LIRIK LAGU “BUKTIKAN” KARYA IWAN FALS ANALISIS SEMIOTIK CHARLES SANDERS - Muhamad Nasir Kaharudin; Wikanengsih Wikanengsih; Riana Dwi Lestari (IKIP Siliwangi, 2021)
Song lyrics are a series of pitched words to be sung as a form of self-expression from a musician. There is a musician's message or social criticism on the song lyrics he creates. Likewise with the song lyrics Buktikan, there is social criticism of the song lyrics. Because the lyrics of this song Buktikan by Iwan Fals have deep social criticism, the authors make the lyrics of this song as research material. The author formulates any social critism contained in the song lyrics Buktikan. The purpose of this study is to describe the social criticism of the results of the song analysis. The method used is a qualitative descriptive method which is carried out by describing the lyrics of the song and then examined using Charles Sanders Pierce's semiotic approach by means of sign, reference sign (object), and use of signs (interpretant) so that social criticism of the lyrics of this song can be known. The results of this research that become a sign are song lyrics Buktikan, then the object is the social context of the songwriter, and what becomes the interpretant is the result of lowering the song lyrics to a certain meaning. The social criticism contained in the lyrics of this song is criticism that focuses on the government not only to break promises, but also needs to prove it.